2014
DOI: 10.1002/hed.23743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on the incidence of head and neck cancer in diabetics

Abstract: Metformin is associated with a lower risk of developing head and neck cancer in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 30 publications
0
73
1
1
Order By: Relevance
“…The studies were conducted in 2 different countries: the United States of America [9,20] and Taiwan [21]. All 3 studies were published recently (1 article in 2012 and 2 articles in 2014) and were written in English.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were conducted in 2 different countries: the United States of America [9,20] and Taiwan [21]. All 3 studies were published recently (1 article in 2012 and 2 articles in 2014) and were written in English.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This process led to exclusion of 21 studies (Appendix 2, [56][57][58][59][60][61][62][63][64][65]). In the end, only 3 articles [9,20,21] were selected. A flow chart detailing the process of identification, inclusion, and exclusion of studies is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with current study, some previous studies have reported a decreased cancer risk among metformin users. However, the protective effect of metformin use on HNC is not conclusive [21,22]. Sikka et al [28] demonstrated that metformin may inhibit cell growth in squamous cell carcinoma of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the association between DM and the risk of HNC that take into account metformin use have also reported conflicting results. A Taiwanese study reported a decreased risk of HNC among metformin users (adjusted hazard ratio = 0.66; 95% confidence interval [CI] 0.55-0.79) [21], while another study in the United Kingdom reported no association [22].…”
Section: Introductionmentioning
confidence: 99%